IMPLEMENTASI NILAI MULTIKULTURAL DALAM MEMBENTUK INTERAKSI INKLUSI - Bhala, Dolorestin Monika; Romadhon, Romadhon; Kukuh Widijatmoko, Engelbertus (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2025)
Multicultural education is a progressive approach in the education system aimed at identifying, addressing, and eliminating inequalities, failures, and discriminatory practices. In the context of higher education, multicultural education plays a crucial role in developing understanding and appreciation of cultural diversity among students. This study reveals that although multicultural education has been integrated into education policies in many countries, its implementation is often uneven and ineffective in addressing the gaps between ethnic or cultural groups. The primary factor hindering the effectiveness of multicultural education is the lack of a deep understanding of the culture and specific needs of each ethnic group. Additionally, the gaps and discrimination that still occur on campuses reflect the need for stronger commitment from educators, policymakers, and the entire academic community to create an inclusive learning environment. Through sustained commitment and a holistic approach, multicultural education can have a significant positive impact in shaping a more tolerant, just, and harmonious society